RETRACTED: THE EVALUATION OF SURROGACY’S LEGAL SYSTEM IN INDONESIA AS COMPARISON TO INDIA’S LEGISLATION - Mega Dewi Ambarwati; Ghina Azmita Kamila (Fakultas Hukum, Universitas Diponegoro, 2019)
This article has been retracted from the journal Diponegoro Law Review Vol. 4 No. 2, October 2019.Please refer to the article THE EVALUATION OF SURROGACY’S LEGAL SYSTEM IN INDONESIA AS COMPARISON TO INDIA’S LEGISLATION on the following link: https://jurnal.unej.ac.id/index.php/eJLH/article/view/10842